Copper chloride‐doped polyaniline/multiwalled carbon nanotubes nanocomposites: Superior electrode material for supercapacitor applications. Issue 4 (13th March 2013) - Dhibar, Saptarshi; Sahoo, Sumanta; Das, C.K.
Abstract In this study, copper chloride (CuCl2)‐doped polyaniline (PANI)/multiwalled carbon nanotubes (MWCNTs) nanocomposite (PANI C2 CNT), CuCl2‐doped PANI (PANI C2) and pure PANI was synthesized by in situ oxidative polymerization method, using ammonium peroxodisulfate as oxidant in HCl medium. These composites were investigated as electrode materials for supercapacitors. The interaction of metal cation (Cu2+) with PANI was confirmed by Fourier transform infrared spectroscopy. The morphology of the composites was characterized by field‐emission scanning electron microscopy and high‐resolution transmission electron microscopy analysis. Electrochemical characterizations of the materials were carried out by three electrode probe method, where platinum and saturated standard calomel electrode were used as counter and reference electrode, respectively. 1 M KCl solution was used as electrolyte for all the electrochemical characterizations. The transition metal ion doping enhanced the electrochemical properties of the conducting polymer. Among all the composites, CuCl2‐doped PANI/MWCNT showed highest specific capacitance value of 724 F/g at 10 mV s−1 scan rate. The Nyquist plot of the polymeric materials showed low equivalent series resistance of the electrode materials. Thermal stability of the composites was examined by thermogravimetric analysis.POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers